PENANGGULANGAN PERNIKAHAN ANAK DENGAN PENDEKATAN HUKUM ADAT DI PULAU LOMBOK PROVINSI NUSA TENGGARA BARAT - Ida Surya (STIS Darussalam Bermi, 2025)
The province of West Nusa Tenggara, which consists of two islands (Lombok and Sumbawa), has 8 regencies and 2 cities with its capital in Mataram. It is one of the provinces in Indonesia, and its vision and mission is to lead its people towards prosperity, as outlined in the vision and mission of the province of West Nusa Tenggara, namely: ‘Moving forward’ is the vision of the Acting Governor of West Nusa Tenggara in leading the provincial government to make West Nusa Tenggara more advanced and move forward with a stronger accelerative spirit. The West Nusa Tenggara government continues to develop and advance the region. Its efforts for a more advanced West Nusa Tenggara are not merely about appearance but also about acceleration. West Nusa Tenggara is ready to continue moving forward and become an even better province in the future. However, in implementing this vision and mission, West Nusa Tenggara faces significant challenges related to achieving the well-being of its people, particularly the high rate of early marriage. This is a major issue in West Nusa Tenggara and requires special attention to resolve it, ensuring that the people of West Nusa Tenggara can achieve their well-being. The objectives of this study are: 1. To analyse the causes of child marriage, 2. To understand local wisdom and the role of local governments in addressing child marriage, 3. To analyse the challenges faced in addressing child marriage. This research employs a qualitative research approach. Data collection methods include interviews, documentation, observation, and literature review. Child marriage occurs due to several factors, including technology, such as smartphones, as most children now own Android smartphones, leading to free-wheeling social interactions. There is also a lack of clear guidelines addressing this issue, and there is a need for a Memorandum of Understanding (MOU) between traditional leaders, community leaders, and the local government to reduce the incidence of child marriage.